La adopción de la teoría copernicana por Kepler: un caso de interacción entre ciencia, filosofía y religión - Kozhamthadam, Job (2005)
lt is well known that Johannes Kepler was one of the first reputed and professionally recognized scientists to support the new heliocentric theory of Copemicus. Kepler accepted lt not as a provisional simpler theory, but as the true theory of the universe, and he did so despite the fact that he, more than any one else at that time, was keenly aware of the defects and deficiencies of this new theory. This paper Is an attempt to shed sorne fresh light on this baffling puzzle. After carefully and crltically examining the different views of well-recognized Ke pler scholars, this paper traces the source of this enigma to his special mode of thinking and proceedlng in his sclentlfic inquiry: Kepler allowed a creative and constructlve interaction between scientiflc data, phllosophical principies and certain religious beliefs. lf he had relied on empirícal data alone, he would not have been the most Ioyal Copemican. Philosophical or religious ideas alone also would not have convinced him of the veracity of the heliocenlríc view. Kepler's acceptance of the Copemican system is a paradigm lnstance of the constructive interaction between science, philosophy and religion in the history of science.